Perceptions of Public Debt Management Offices on The Impact of Public Debt On Economic Growth in Low and Middle-Income Countries - El Mehdi, Chakir; Noufail Outmane, Soussi (Ekonomika, 2025)
This study explores perceptions of public debt management among Debt Management Offices (DMOs) in low- and middle-income countries. Based on a survey conducted in October 2023 covering 27 countries, it examines DMOs’ views on the relationship between public debt and economic growth, the practices shaping these perceptions, and the key variables influencing debt dynamics through regression modelling.The study findings highlight that DMOs generally perceive debt as negatively impacting growth, with perceptions shaped more by professional experience than internal economic studies. Four critical variables – debt cost, economic growth, primary deficit, and governance – emerge as key influences. Notably, DMOs conducting in-house studies show more cautious assessments than those relying solely on experience or external studies. These insights provide a nuanced understanding of debt dynamics, incorporating the subjective yet practical perspectives of debt managers.